PENERAPAN METODE INDEX CARD MATCH DENGAN MEDIA FLANELGRAF DALAM PENINGKATAN PEMBELAJARAN IPS PADA SISWA KELAS V SD - Muniroh, Syarifatul (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Application of Index Card Match Learning Method with Flannel Graph Media In Improving Social Studies Learning at the Fifth Grade Students Elementary School. The purpose of this research is to describe the application of Index Card Match learning method with flannelgraph media, improving social studies learning, and to describe the problems and solutions on the application of Index Card Match method with flannel graph media. This research that carried out in three cycles. Every cycle consisting of two a meetings consisting of planning, action, observation and reflection. This research is a classroom action research in three cycle, each cycle includes of planning, action, observation, and reflection. The subjects were elementary school students in V grade state Kenoyojayan, with total 20 students. The result of research shows that the application of Index Card Match learning method with flannelgraph media could improving social studies learning at V grade student. Keywords: Index Card Match, flannelgraph media, learning, social studies Abstrak: Penerapan Metode Index Card Match dengan Media Flanelgraf dalam Peningkatan Pembelajaran IPS pada Siswa Kelas V SD. Tujuan penelitian ini adalah untuk mendeskripsikan langkah-langkah penerapan metode pembelajaran Index Card Match dengan media flanelgraf, meningkatkan pembelajaran IPS, dan mendeskripsikan kendala dan solusi penerapan metode pembelajaran Index Card Match dengan media flanelgraf. Penelitian ini dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari dua pertemuan terdiri dari: perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjeknya adalah siswa kelas V SDN Kenoyojayan, dengan jumlah 20 siswa. Hasil penelitian ini menunjukkan bahwa penerapan metode pembelajaran Index Card Match dengan media flanelgraf dapat meningkatkan pembelajaran IPS kelas V. Kata Kunci: Index Card Match, media flanelgraf, pembelajaran, IPS